Predictive clinical factors of cystoid macular edema in patients with Descemet’s stripping automated endothelial keratoplasty - Koji Kitazawa (Nature Portfolio, 2017)
Abstract The purpose of this present study was to investigate predictive clinical factors associated with cystoid macular edema (CME) post Descemet’s stripping automated endothelial keratoplasty (DSAEK) in a large case series. Of 393 consecutive patients who underwent DSAEK at Baptist Eye Institute, Kyoto, Japan between July 2011 and November 2016, 241 patients without CME at the pre- or early-postoperative periods were enrolled. The occurrence of anatomic CME was prospectively examined via optical coherence tomography (OCT). Possible predictive clinical factors for CME were analyzed by multivariate logistic regression analysis. At 1-month post DSAEK, CME occurred in 27 (11.2%) of the 241 patients. Multivariate analysis revealed that primary angle closure glaucoma (PACG) was significantly associated with postoperative CME (odds ratio = 6.4, P = 0.04). The findings of this study revealed that DSAEK in patients with PACG showed a high incidence of CME, thus indicating that they should undergo a careful postoperative observation of the macula via OCT.